Pengaruh Kepercayaan Merek, Promosi, dan Harga terhadap Loyalitas Konsumen pada Bisnis Ritel Kosmetik - Putu Diah Purnamayanti; Indiani, Ni Luh Putu (Jurnal Penelitian Ekonomi Akuntansi, 2024)
Women's cosmetics retail competition in Bali is growing rapidly, especially in Badung Regency. Intense competition encourages retail businesses to intensively increase consumer loyalty. This has led to interest in analyzing the factors that influence consumer loyalty to cosmetic retail stores in Badung. This study aims to determine the effect of brand trust, promotion and price on consumer loyalty. The population in this study is all customers of the cosmetic industry in Badung Regency. The study obtained 95 valid samples. Sampling using accidental random sampling technique. The data analysis technique uses multiple linear regression analysis. From the results of the study, it was found that brand trust, promotion, and price have a positive and significant effect on consumer loyalty. Aspects that need to be considered to increase brand trust, cosmetic retail stores need to offer quality beauty products, maintain a good reputation, offer products that can be relied on by consumers, offer beauty products according to the concept of consumer personality, and increase positive recommendations from consumers. To increase promotions, retail stores need to promote on social media regularly, implement quality promotions, and implement the right promotions for consumers such as following emerging trends. To provide the best price to consumers, retail stores need to make product price policies that are competitive compared to similar products elsewhere, making product price policies that are in accordance with the benefits obtained by consumers.